2012
DOI: 10.1016/j.alcohol.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Recognized spontaneous abortion in mid-pregnancy and patterns of pregnancy alcohol use

Abstract: Alcohol consumption during pregnancy is one potential risk factor for spontaneous abortion (SAb). Prior research suggested that heavy drinking during pregnancy was associated with significantly increased rates of SAb, but results for lower levels of drinking have been inconsistent. We examined the association between different levels and patterns of prenatal alcohol consumption and SAb in a high-risk inner-city sample. We hypothesized that higher levels, binge patterns, and more frequent drinking would be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 63 publications
(92 reference statements)
4
26
0
7
Order By: Relevance
“…However, the literature has yielded inconsistent results regarding the existence of an association. Several studies have found an association between alcohol consumption during pregnancy and miscarriage(Andersen, Andersen, Olsen, Gronbaek, & Strandberg-Larsen, 2012; Armstrong, McDonald, & Sloan, 1992; Chiodo et al, 2012; Harlap & Shiono, 1980; Henriksen et al, 2004; Kesmodel, Wisborg, Olsen, Henriksen, & Secher, 2002; Kline, Shrout, Stein, Susser, & Warburton, 1980; Maconochie, Doyle, Prior, & Simmons, 2007; Rasch, 2003; Windham, Von Behren, Fenster, Schaefer, & Swan, 1997). However, others, including two systematic reviews published in 2006 and 2007, have not(Cavallo, Russo, Zotti, Camerlengo, & Ruggenini, 1995; Henderson, Gray, & Brocklehurst, 2007; Parazzini et al, 1994; Tolstrup et al, 2003; Zhang & Bracken, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature has yielded inconsistent results regarding the existence of an association. Several studies have found an association between alcohol consumption during pregnancy and miscarriage(Andersen, Andersen, Olsen, Gronbaek, & Strandberg-Larsen, 2012; Armstrong, McDonald, & Sloan, 1992; Chiodo et al, 2012; Harlap & Shiono, 1980; Henriksen et al, 2004; Kesmodel, Wisborg, Olsen, Henriksen, & Secher, 2002; Kline, Shrout, Stein, Susser, & Warburton, 1980; Maconochie, Doyle, Prior, & Simmons, 2007; Rasch, 2003; Windham, Von Behren, Fenster, Schaefer, & Swan, 1997). However, others, including two systematic reviews published in 2006 and 2007, have not(Cavallo, Russo, Zotti, Camerlengo, & Ruggenini, 1995; Henderson, Gray, & Brocklehurst, 2007; Parazzini et al, 1994; Tolstrup et al, 2003; Zhang & Bracken, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating alcohol consumption in continuous or discrete levels of intake have produced more mixed results(Andersen, et al, 2012; Armstrong, et al, 1992; Cavallo, et al, 1995; Chiodo, et al, 2012; Harlap & Shiono, 1980; Henriksen, et al, 2004; Kesmodel, et al, 2002; Kline, et al, 1980; Maconochie, et al, 2007; Parazzini, et al, 1994; Rasch, 2003; Windham, Fenster, & Swan, 1992; Windham, et al, 1997). Most research examining levels of alcohol use has found evidence of a threshold between two to four drinks per week at which alcohol use during pregnancy is related to miscarriage(Andersen, et al, 2012; Armstrong, et al, 1992; Harlap & Shiono, 1980; Henriksen, et al, 2004; Kesmodel, et al, 2002; Kline, et al, 1980; Maconochie, et al, 2007; Rasch, 2003; Windham, et al, 1992; Windham, et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that treatment with NMDA blockers and GABAA agonists can lead to respiratory depression in neonates (Fregosi et al, 2004;Poon et al, 2000), which in turn, is commonly associated with hypoxia, a lack of adequate oxygen supply that can cause death or severely affect brain development (Nyakas et al, 1996). Moreover, it is well known in humans that the number of miscarriages (Chiodo et al, 2012) as well as the severity of pathological phenotypes in the newborn (Riley and McGee, 2005) increase as the amount of ethanol consumed increases. Thus, it may be unclear as to whether the behavioral changes observed in the MK HIGH and MK LOW +MU HIGH groups were a result of the diminished health of the animal, a direct effect of the drug on the brain, or some combination of these factors.…”
Section: Discussionmentioning
confidence: 98%
“…O efeito tardio se manifesta por mudanças na capacidade intelectual, de aprendizagem, atenção e comportamento 2 . Estudos recentes [3][4][5] mostram que não existe uma quantidade de consumo alcoólico que possa ser considerada segura durante a gravidez, e que as mulheres deveriam ser aconselhadas à abstinência alcoólica desde a concepção e durante todo o período de gravidez.…”
Section: Introductionunclassified